Patterns and Trends in Chlorophyll-a Concentration and Phytoplankton Phenology in the Biogeographical Regions of Southwestern Atlantic - Delgado, Ana Laura (2023)
The Southwestern Atlantic Ocean (SWA), is considered one of the most productive areas of the world, with a high abundance of ecologically and economically important fish species. Yet, the biological responses of this complex region to climate variability are still uncertain. Here, using 24 years of satellite-derived Chl-a data, we classified the SWA into 9 spatially coherent regions based on the temporal variability of Chl-a concentration, as revealed by SOM (Self-Organizing Maps) analysis. These biogeographical regions were the basis of a regional trend analysis in phytoplankton biomass, phenological indices, and environmental forcing variations. A general positive trend in phytoplankton concentration was observed, especially in the highly productive areas of the northern shelf-break, where phytoplankton biomass has increased at a rate of up to 0.42 ± 0.04 mg m−3 per decade. Significant positive trends in sea surface temperature were observed in 4 of the 9 regions (0.08–0.26 °C decade−1) and shoaling of the mixing layer depth in 5 of the 9 regions (−1.50 to −3.36 m decade−1). In addition to the generally positive trend in Chl-a, the most conspicuous change in the phytoplankton temporal patterns in the SWA is a delay in the autumn bloom (between 15 ± 3 and 24 ± 6 days decade−1, depending on the region). The observed variations in phytoplankton phenology could be attributed to climate-induced ocean warming and extended stratification period. Our results provided further evidence of the impact of climate change on these highly productive waters.